Quality of service and service level agreement in the cloud computing - Maarouf, Adil (Université HASSAN 1er, Faculté des Sciences et techniques-Settat., 2017)
The revolutionary technology of Cloud Computing offers a scalable and flexible paradigm where infrastructure, platform, and software are offered to users in the form of services. The management of such environment is inherently complex due to the large-scale number and heterogeneity of resources and the increasing number and types of services the cloud must deliver over the Internet. However, due to the highly dynamic nature of this open environment, it is important to have a binding agreement between all the service parties for ensuring trust while fulfilling the expected Quality of Service (QoS). The provisioning of these computing services by cloud providers are regulated by Service Level Agreements, which present an important element that provides some degree of assurance. In this context, SLA contract forms an appropriate solution to specify these QoS guarantees. It specifies one or more service level objectives (SLO), to guarantee that the delivered QoS satisfies the consumer expectations. To properly operate and manage such complex situations, in this thesis, our main ob- jectives are to propose an efficient method for automation of SLA contract establishment process, and to provide an autonomic SLA monitoring mechanism managed by a trusted third party for real time ensuring accountability and QoS in cloud services. Firstly, for automating SLAs contract establishment, we investigate this issue and propose our conception by using Model Driven Engineering (MDE) to express the SLA contract requirements, as a mean for establishing service level agreements between a cloud provider and cloud customer in the context of a particular service provision. The cloud SLA contract language we present is a meta-model for defining cloud SLAs specifically defined for the cloud computing domain, that supports most of the characteristics of cloud. We evaluate the completeness and clarity of our SLA contract establishment for Conceptual Modeling with Bunge-Wand-Weber representational theory. We also validate our meta-model to examine the ability of the proposed SLA establishment approach to generate the SLA document in less time. Secondly, we propose a Novel Penalty Model for calculating the penalty cost of the viola- tions, that can efficiently help for managing and applying penalties in the cloud computing. Lastly, we propose an autonomic SLA monitoring framework managed by trusted third party composed of two modules: the first one SLA establishment module, which aims at providing support for automated SLA generation and management. The second one, a service monitoring module to dynamically monitor QoS metrics by detecting SLA violations at runtime to verify compliances for the respective SLAs, and to propose a mechanism for an adaptive remedy rectification. The trusted third party framework equipped with such reputation module can provide real-time assessment for consumers informed decision making to continue using a service or to migrate to another service provider in the case of service degradation. This creates a fair competitiveness between providers and hence improves service performance and the reliability in the cloud.
Keywords: Cloud Computing; Service Level Agreement; Quality of Service; Model Driven Engineering; Autonomic SLA Monitoring; Trusted Third Party; Autonomic MAPE-K Cycle; Violation; Penalty Cost Calculation; Reputation.